Arnold Hauser, Walter Benjamin and the mythologization of history - Puerto, César Saldaña (Journal of art historiography, 2020)
[...]if Benjamin posthumously grew to become a major author associated with the Frankfurt School,2 Hauser remained an outsider, whose figure has, ever since, faded and re-emerged with dubious fortune.3 In spite of opposite lucks, both authors were marked by a strong anti-positivistic attitude which sought to establish a distinct methodology for the social sciences, striving to understand the present through art criticism. Comparing their concepts for totality, the purpose that guided them, and some significant affinities in process of inquiry, writing style, and choice of subject-matter, it becomes apparent that their art criticism handles historical narrative as myths, rendering their methods close to psychoanalytical dream interpretation. To him, philosophy, science, law, custom, and art are different aspects of one unitary attitude to reality: in all these forms men are searching for an answer to the same question, for a solution to one and the same problem of how to live.7 The object of study, although it is referred to through a great variety of concepts -'totality', 'society', 'worldview' - ultimately implies inquiring into the 'solution given to the problem of how to live'. Benjamin thought, as did Hauser, that demarcating fields of specialization improves accumulation in the autonomous spheres; but this process of progressive autonomization contributes to what these authors called the 'reification of knowledge': accuracy of details comes at the expense of the capacity of synthetical interpretation, which is delayed, bringing also the stiffening of methodology, all of which Adorno described in terms of paralysis.8 As Jürgen Habermas recalls, Benjamin expressed a similar distress towards knowledge-accumulation: "Cultural history, to be sure, increases the weight of the treasure which accumulates on the back of humanity.